Модель силового преобразователя асинхронного электропривода электромобиля в режиме рекуперативного торможения - Пшеничников, Дмитрий Алексеевич; Воробьёв, Богдан Витальевич (НТУ "ХПИ", 2019)
Построена компьютерная модель асинхронного электропривода электромобиля с суперконденсаторной батареей в качестве промежуточного звена накопления электрической энергии торможения и развёрнутой моделью преобразователя частоты. Проведено компьютерное моделирование переходных процессов в преобразователе частоты при движении электромобиля по прямой и со склона. Получены переходные характеристики в ключах преобразователя, а также общие переходные процессы электропривода в режимах городского цикла движения транспорта и рекуперативного торможения.

A computer model of an asynchronous electric drive of an electric vehicle with a supercapacitor battery as an intermediate link of accumulation of electric braking energy and a expanded model of a frequency converter is constructed. An electric vehicle electric drive function block diagram is designed according to energy transformation character during movement of an according. Optimum on power parameters and regulating and mechanical characteristics the structure of the modern frequency-adjustable electric drive with the asynchronous motor includes autonomous voltage inverter with power IGBT transistors and control system. Pulse width modulation principle is used for formation of output current. By development of mathematical model of the frequency converter includes mathematical description of processes only in a power unit as nonlinear pulse system. A computer simulation of transients in the frequency converter during the movement of an electric vehicle in a straight line and from a slope was conducted. Transient characteristics were obtained in converter switches, as well asgeneral transients of the electric drive in the modes of the urban cycle of traffic with regenerative braking.
Asynchronous electric drive power converter model of an electric vehicle in regenerative braking mode
Keywords: суперконденсатор; энергосбережение; частота; переходные процессы; электрическая энергия; supercapacitor; saving energy